Mudas de cafeeiro (Coffea arábica L.) desenvolvidas sob fontes de material orgânico no substrato comercial - Silva, Cícero José da (2010)
This study evaluated the development of coffee seedlings (Coffea arabica L.) under five proportions (0, 15, 30, 45 and 60% v/v) of three sources of organic material (cattle manure, poultry manure and forest humus) added to the commercial substrate Bioplant® coffee. The experimental design was randomized blocks, with four repetitions, in factorial scheme. The experiment was conducted in nursery with shade 50% of natural light in Orizona county, Goiás, Brazil, from September 2008 to March 2009. Seeds the cultivar Catuaí Vermelho IAC-144 were sown at 1.0 cm of deep, using two seeds per 11 x 20-cm container (bag). The evaluations of plant height, stem diameter and number of leaves were done at 120, 160 and 210 days after sowing. The evaluations of main root length, dry matter of aerial part and roots, total dry matter, ratio root dry matter/aerial part were done only at 210 days. Tukey s test was applied for compare the sources and the regression analysis to estimate the best proportion and points of maximum s equations. The results indicated significant interaction of organic matter proportion and sources. On average, cattle manure provided better results for all characteristics evaluated, while the zero dose (commercial substrate alone) yielded the worst results. The greatest plant heights were estimate in 19.4, 16.4 and 13.8 cm, with the proportion of 33.5%, 36.0% and 52.8%, of poultry manure, cattle manure and forest humus, respectively, at 210 days. The greatest stem diameters were calculate as 4.3 and 4.4 mm, with the proportion of 32.7% and 36.1% of poultry manure, cattle manure and forest humus, respectively, at 210 days. The greatest average leaf numbers were 7.7, 8.0 and 7.2, computed with the proportion of 33.8%, 37.1% and 48.1%, of poultry manure, cattle manure and forest humus, respectively, at 210 days. The maximum root length was estimated as 22.7, 21.8 and 22.2 cm, with the proportion of 15.5%, 13.3% and 34.2% of poultry manure, cattle manure and forest humus, respectively. The greatest aerial part dry matter was estimate as 3.3 and 2.5 g plant-1, with the proportion of 32.7% and 36.1% of poultry manure and cattle manure, respectively. The greatest root dry matter amounts were calculate as 1.6 and 1.4 g plant-1, with the proportion of 32.7% and 36.1% of poultry manure and cattle manure, respectively. The mixture of forest humus to the substrate provided a linear growth response for stem diameter and dry matter of roots and aerial part.